(untitled) (Revista Latino-Americana de Enfermagem, 2010)
Demand for the Emergency Department (ED) has increased, making the organization of work difficult. This quantitative, descriptive and documental study identifies and analyzes the characteristics of clinical care in the ED of a General Hospital in Ribeirão Preto, SP, in 2007, according to organizational variables. The study population included all clinical care consultations registered in the Hospital Management Information System. Data were analyzed through descriptive statistics and discussed considering the theoretical framework of the Single Health System (SUS). A total of 5,285 consultations were registered in the period, which were more frequent in patients from the city itself, in January (10%), on Mondays (16%), from 12pm to 12am (67.1%). The main reason for discharge from the unit was hospitalization (63.8%) and the predominant length of stay in the unit was less than six hours (39.8%). The results support the management of human resources, materials and equipment, indicating the desirability of reorganizing emergency care in the hospital.